STRATEGI AGILITY PADA COMPETITIVE ADVANTAGE LAUNDRY COIN DALAM PERSFEKTIF EKONOMI ISLAM - Triani, Lita; Nursya'adah, Alya Aulia; Rifaldi, Muhammad; Sanjaya, Vicky F (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
Coin laundry business is one form of service business that is growing rapidly in the modern era. To survive in tight competition, agility strategy is one of the relevant approaches. This article discusses how agility can be applied to improve the competitive advantage of coin laundry business from an Islamic economic perspective. By focusing on sharia principles such as fairness, transparency, and benefit, this study outlines innovation, flexibility, and collaboration strategies that can be adopted.